A mixed-methods approach to understanding partnership experiences and outcomes of projects from an integrated knowledge translation funding model in rehabilitation - Jacqueline Roberge-Dao; Brooks Yardley; Anita Menon; Marie-Christine Halle; Julia Maman; Sara Ahmed; Aliki Thomas (BMC, 2019)
Abstract Background Integrated knowledge translation (IKT) can optimize the uptake of research evidence into clinical practice by incorporating knowledge users as equal partners in the entire research process. Although several studies have investigated stakeholder involvement in research, the literature on partnerships between researchers and clinicians in rehabilitation and their impact on clinical practice is scarce. This study described the individual research projects, the outcomes of these projects on clinical practice and the partnership experiences of an initiative that funds IKT projects co-led by a rehabilitation clinician and a researcher. Methods This was a sequential explanatory mixed methods study where quantitative data (document reviews and surveys) informed the qualitative phase (focus groups with researchers and interviews with clinicians). Descriptive analysis was completed for the quantitative data and thematic analysis was used for the qualitative data. Results 53 projects were classified within multiple steps of the KTA framework. Descriptive information on the projects and outcomes were obtained through the survey for 37 of the 53 funded projects (70%). Half of the respondents (n = 18) were very satisfied or satisfied with their project's impact. Only two (6%) projects reported having measured sustainability of their projects and four (11%) measured long-term impact. A focus group with six researchers and individual interviews with nine clinicians highlighted the benefits (e.g. acquired collaborative skills, stronger networks between clinicians and academia) and challenges (e.g. measuring KT outcomes, lack of planning for sustainability, barriers related to clinician involvement in research) of participating in this initiative. Considerations when partnering on IKT projects included: the importance of having a supportive organization culture and physical proximity between collaborators, sharing motives for participating, leveraging everyone's expertise, grounding projects in KT models, discussing feasibility of projects on a restricted timeline, and incorporating the necessary knowledge users. Clinicians discussed the main outputs (scientific contribution, training and development, increased awareness of best practice, step in a larger effort) as project outcomes, but highlighted the complexity of measuring outcomes on clinical practice. Conclusion The study provides a portrait of an IKT funding model, sheds light on past IKT projects' strengths and weaknesses and provides strategies for promoting positive partnership experiences between researchers and rehabilitation clinicians.